Leaf anatomy studies of the genus Saraca L. (Fabaceae) in India - Raj, Patturaj; Ravikumar, K.; Noorunnisa Begum, S. (Current Botany, 2025)
Anatomical studies on leaves and petioles were carried out for four species of Saraca L. found in India, focusing on microscopic characters based on an anatomical key and a dendrogram (phylogenetic) tree is provided. The distinguishing characters of the leaf revealed the presence of mesophyll length of palisade and spongy parenchyma, size of xylem vessels, type, and number of stomata, presence and absence of crystals and oil glands. In the petiole, the overview shape, number of vascular bundles, types, layers of sclerenchyma, shape of epidermis, etc. are discussed. Among the thirty-five microscopic characters, the signified diversity of each species with qualitative and quantitative data of the anatomical character has been investigated through numerical cluster analysis method by to the UPGMA. An organized petiole anatomical character based on the anatomical keys can play a pivotal tool for taxonomic delimitation and comparison between each of the species.